REPRESENTASI EMANSIPASI WANITA DALAM SEKSUALITAS NOVEL DR UPADI KARYA SUJIWO TEJO: KRITIK SASTRA FEMINIS - Akhirul Insan Nur Rokhmah; Edi Suryanto (Kajian Linguistik dan Sastra, 2022)
The development of feminism in Indonesia began in the time of colonialism when revolutionaryheroines defended the country. Female emancipation began to emerge since the existence ofRaden Ajeng Kartini who was actually a capable woman and could get a higher education.Feminism provides an understanding of the women's point of view itself so as to correct theinequality of non-feminist societies. The discourse of sexuality in the novel “Dr Upadi” uses thepoint of view of ars erotica where sexuality will be seen as an aesthetic element in a literarywork. The type and design used in this study is descriptive-qualitative research. This study takesa radical feminist literary criticism approach where the flow rests on the order of women causedby patriarchy. Radical feminists will give people awareness on the issue of rape and violenceagainst women. The results of the study conducted in the novel “Dr Upadi” by Sujiwo Tejoresulted in the conclusion that there are 18 dictions and phrases of sexuality, each of which playsa role as a woman's attractiveness and the ability of women to dominate, hide feelings, defendwomen's rights in oppression, women's strength to overcome the situation of the superior male,the obstinacy of the female, as well as the debilitating weakening of sexuality.Keywords: literary criticism, radical feminism, sexuality discourse, Sujiwo Tejo's novel "Dr Upadi"